Period: The real story of menstruation - Clancy, Kate (Princeton Princeton university press, 2023)
An exploration on the science and cultural history of menstruation that challenges many of the myths and false assumptions that have defined the study of the uterus. Covers issues such as bodily autonomy, menstrual hygiene, the COVID-19 vaccine, and the ways racism, sexism, and medical betrayal warp public perceptions of menstruation.
Keywords: Women's rights; Menstruation aspect social; Cycle menstruel aspect social